D’autres mondes pour d’autres musiques : les dimensions sonores parallèles de The OA (Partie 01) - Jérémy Michot (ReS Futurae)
The OA, a television series created by Brit Marling and Zal Batmangli (Netflix 2016-2019), features Prairie a young missing woman who reappears after seven years of absence. She tells her story to four highschool students and a teacher, in the dim light of an abandoned house : family drama, sequestration, near-death experience, journey between dimensions, multiverse, encounter with cosmic or lovecraftian creatures are at the center of memories as well as stories that Prairie offers to its listeners during part 1. This article explores how sound and music contributes to the OA’s character and distrubing narrative. On one hand, by analyzing minimalistc musical textures, they refer to other series as well as science-fiction cinema. On the other hand, showing music and other diegetic sound effects appearing at the heart of the plot, as territories embodied by sound.